BS EN ISO 11239. Health informatics. Identification of medicinal products. Data elements and structures for the unique identification and exchange of regulated information on pharmaceutical dose forms, units of presentation, routes of administration and packaging. (29th September 2022) - British Standards Institution,
No abstract available